2013
DOI: 10.1002/jgrd.50423
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical aging of volatile organic compounds in the Los Angeles basin: Weekday‐weekend effect

Abstract: [1] During the CalNex (California Research at the Nexus of Air Quality and Climate Change) field study in May-June 2010, measurements of volatile organic compounds (VOCs) were performed in the Los Angeles (LA) basin onboard a NOAA research aircraft and at a ground site located in Pasadena. A weekday-weekend effect in ozone, caused by lower NO x emissions due to reduced diesel truck traffic in the weekends, has been previously observed in Los Angeles and other cities. Measurements in the Caldecott tunnel show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
86
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 57 publications
7
86
0
1
Order By: Relevance
“…Other VOCs besides HCHO that were emitted by traffic and other local sources may also have contributed to the photochemical production of O 3 , but they were not quantified. Similar differences of O 3 and O x mixing ratios between weekdays and weekends were reported in the South Coast Air Basin (Pollack et al, 2012;Warneke et al, 2013). Temperature also affects O 3 production, but given the great variation of O 3 mixing ratio through the day, this was a secondary effect here based on box model calculations in the temperature range of our study (Coates et al, 2016).…”
Section: O 3 No No 2 and Hchosupporting
confidence: 80%
“…Other VOCs besides HCHO that were emitted by traffic and other local sources may also have contributed to the photochemical production of O 3 , but they were not quantified. Similar differences of O 3 and O x mixing ratios between weekdays and weekends were reported in the South Coast Air Basin (Pollack et al, 2012;Warneke et al, 2013). Temperature also affects O 3 production, but given the great variation of O 3 mixing ratio through the day, this was a secondary effect here based on box model calculations in the temperature range of our study (Coates et al, 2016).…”
Section: O 3 No No 2 and Hchosupporting
confidence: 80%
“…The weekend-weekday effect typically relies on the assumption that the VOC reactivity and thus HO x production are unchanged between the weekend and weekdays. However, this is not always the case, as decreased weekend NO x re- duces NO x +OH reactions and thereby increases weekend OH and O 3 (Warneke et al, 2013). Few studies of VOCs in the NFRMA exist, but our previous work found no significant difference in measured VOC reactivity at the BAO site between weekends and weekdays in summer 2015 .…”
Section: Weekend-weekday Effect In Denver Comentioning
confidence: 76%
“…This effect can be used to elucidate information about local chemical regimes (i.e., CARB, 2003;Murphy et al, 2007;Fujita et al, 2003;Warneke et al, 2013;Pollack et al, 2012;Cleveland et al, 1974;Heuss et al, 2003). Traffic patterns in urban regions are different between weekends and weekdays from a decrease in heavy-duty truck traffic on weekends (Marr and Harley, 2002).…”
Section: Weekend-weekday Effect In Denver Comentioning
confidence: 99%
“…The highest relative abundances of organic acids were observed in the DenverJulesburg Basin and are likely due to primary emissions from concentrated animal feeding operations and not photochemistry (Eilerman et al, 2016;Yuan et al, 2017). Figure 4 compares the distribution of oxygenates to that measured during the Uintah Basin Winter Ozone Study (UB-WOS) 2013 campaign (Utah Division of Air Quality, 2014), the SENEX and CalNex flights, and the CalNex ground site in Los Angeles (Veres et al, 2011;Warneke et al, 2013). The mix of VOC precursors from oil and gas fields (dominated by small alkanes) is very different from urban and biogenically influenced air.…”
Section: Overview Of H 3 O + Tof-cims Measurementsmentioning
confidence: 99%
“…We used the ratios of toluene, C8 aromatics, and C9 aromatics to benzene to calculate a relative OH exposure for each transect, in order to explore photochemical aging of other VOCs. This method has been used extensively in atmospheric chemistry Warneke et al, 2013), and details are shown in the Supplement (Sect. S3).…”
Section: Overview Of Measurements In the Permian Basinmentioning
confidence: 99%